Development of Teaching and Learning Tool Kit for Science Subject in Secondary School - Suhaimi, Muhammad Sufyan Harish; Pa'ee, Furzani (Enhanced Knowledge in Sciences and Technology, 2023)
Science, Technology, Engineering and Mathematic (STEM) is a critical important subject to helps students to develop skills like problem solving, critical thinking, independent and think creatively.  However, there are still issues about lack of percentage of students who are interested in taking STEM related subjects. Hence, this study was conducted to provide a development of an effective STEM educational kit that manage to be used as facility in every school in Malaysia, increase students understanding and learning of complex topic in science subject clearly and easily with the aids of educational kit and to help increase students’ interest and motivate them in learning STEM related subjects. The method used in this study are applying the ADDIE instructional design to develop a suitable educational kit. Total of 22 form 3 students, 50 form 4 students and 1 form 5 students from SMK Alauddin Riayat Shah 1 were involve in this research study as respondents. From the data, almost 97 percent of all the respondents understand the explanation delivered by the aids of educational kit and feel happy and enjoy learning using the educational kit. Therefore, this study encourages and suggest more educational kit should be developed to help students to understand easily of science subject and interest in learning STEM related subject even more.